Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1152/ajpheart.1999.277.2.h676
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled NO impacts vascular but not extravascular compartments in postischemic peripheral organs

Abstract: Inhaled nitric oxide (NO) reduces pulmonary hypertension and dampens various aspects of lung inflammation; however, its effects are thought to be restricted to the lung because of its short half-life in biological systems. More recently, however, NO was shown to nitrosylate hemoglobin, albumin, and other plasma molecules to form stable nitrosothiol derivatives and could have an impact on the periphery. We examined whether inhaled NO could have an impact on the two compartments of distal organs, namely, the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…We have also demonstrated that SNO-Hb can sense the physiological O 2 gradient in resistance vessels (small arterioles that control blood flow), thereby coupling the release of vasodilator SNO with regional metabolic needs of the tissue (5). Additional work that supports the importance of SNO-Hb includes the myriad studies of the systemic effects of inhaled NO (25)(26)(27)(28)(29), which raises the levels of endogenous SNO-Hb (16). It is tempting to suggest, moreover, that the hypoxia-increased tissue levels of NO in kidneys of animals that had been treated with NO synthase inhibitors (30) implicate SNO-Hb as the source of the elevated NO.…”
Section: ␤93mentioning
confidence: 71%
“…We have also demonstrated that SNO-Hb can sense the physiological O 2 gradient in resistance vessels (small arterioles that control blood flow), thereby coupling the release of vasodilator SNO with regional metabolic needs of the tissue (5). Additional work that supports the importance of SNO-Hb includes the myriad studies of the systemic effects of inhaled NO (25)(26)(27)(28)(29), which raises the levels of endogenous SNO-Hb (16). It is tempting to suggest, moreover, that the hypoxia-increased tissue levels of NO in kidneys of animals that had been treated with NO synthase inhibitors (30) implicate SNO-Hb as the source of the elevated NO.…”
Section: ␤93mentioning
confidence: 71%
“…Recent observations that the inhalation of NO gas at moderate to high levels (80 ppm) can result in systemic effects have begun to challenge the notion of NO being restricted to paracrine actions. NO gas has been shown to modulate a number of remote physiological and pathophysiological processes including systemic vascular resistance, intestinal blood flow, urinary flow, gastrointestinal I/R injury, and myocardial I/R injury (23)(24)(25)(26). Additionally, it has been reported that modifications of dietary NOx (nitrate and/or nitrite) results in the alteration of systemic NO metabolite levels, and thus impacts physiological processes (11,18,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inhaled NO has been reported to reduce systemic vascular resistance, 7 increase kidney filtration rates, 8 increase aortic cGMP levels, 9 and improve blood flow in intestine after NO synthase inhibitors. 10,11 The latter work has been extended by Cannon and colleagues 12 who reported that after blockade of forearm NO production followed by forearm exercise, NO inhalation greatly improved blood flow. Clearly, the bulk of evidence would support the view that inhaled NO can be transported to peripheral vasculatures.…”
mentioning
confidence: 95%